L-Prime Spectrum of Modules - Ersoy, Bayram Ali; Ralescu, Dan (EUROPEAN SOC FUZZY LOGIC & TECHNOLOGY, 2009)
We investigate the Zariski Topology on the L-prime spectrum of modules consisting of the collection of all prime L-submodules and prove some useful results.
Keywords: L-ideal; L-submodule; L-prime submodule; Special L-submodule; L-Irreducible submodule; L-Prime Spectrum; Zariski topology; Generic point; FUZZY IDEALS; RING; SETS; Automation & Control Systems; Computer Science; Operations Research & Management Science; Mathematics